Surface functionalization: an efficient alternative for promoting the catalytic activity of closed shell gold clusters - Joshi, Krati; Krishnamurty, Sailaja; Dar, Manzoor Ahmad (Physical Chemistry Chemical Physics, 2020)
{Surface functionalization through adsorption of ligands or non-metal atoms is considered to be an interesting and viable approach for tuning the physicochemical properties of gold clusters. Highly stable and magic numbered electronic configurations of thiolate protected gold clusters such as Au-25(SR)(18), Au-38(SR)(24)etc. with intriguing properties are the direct manifestation of the rich chemistry of the Au-S interface. The present investigation discerns the CO oxidation activity of structurally well characterized sulphur functionalized gold cluster anions AumS4-

Size and morphology dependent activity of Cu clusters for CO2 activation and reduction: a first principles investigation - Amin, Seerat; Krishnamurty, Sailaja; Dar, Manzoor Ahmad; Joshi, Krati (ChemPhysChem, 2024)
Various Cu-based materials in diverse forms have been investigated as efficient catalysts for electrochemical reduction of CO2; however, they suffer from issues such as higher over potential and poor selectivity. The activity and selectivity of CO2 electro reduction have been shown to change significantly when the surface morphology (steps, kinks, and edges) of these catalysts is altered. In light of this, size and morphology dependent activity of selected copper clusters, Cun (n=2-20) have been evaluated for the activation and reduction of CO2 molecule. The phase-space of these copper clusters is rich in conformations of distinct morphologies starting from planar, 2D geometries to prolate-shaped geometries and also high-symmetry structures. The binding efficiency and the activation of CO2 are highest for medium sized clusters (n=9-17) with prolate-morphologies as compared to small or larger sized CunCO(2) clusters that are existing mainly as planar (triangular, tetragonal etc.) or highly-symmetric geometries (icosahedron, capped-icosahedron etc.), respectively. The best performing (prolate-shaped) CunCO2 conformations are quite fluxional and also they are thermally stable, as demonstrated by the molecular dynamics simulations. Furthermore, on these CunCO(2) conformations, the step-by-step hydrogenation pathways of CO2 to produce value-added products like methanol, formic acid, and methane are exceptionally favorable and energy-efficient.
Keywords: CO2 activation; CO2 hydrogenation; Copper clusters; Density Functional Theory (DFT); molecular dynamics